The influence of school type and perceived teaching style on students' creativity. (December 2021) - Gu, Xiaojing; Ritter, Simone M.; Koksma, Jur; Dijksterhuis, Ap
Highlights: Examine the influence of school experiences on university students' creativity. Include school types (traditional/religious/alternative) at primary/secondary level. Include perceived Teaching Styles (independence/flexibility/integration/judgment). Uni-students from alternative second-schools score high on divergent thinking. TS in alternative second-schools are perceived high on independence and flexibility. Abstract: School is an excellent place to foster young learners' creative thinking skills. However, the emphasis on creativity varies among schools. In two studies the putative influence of school education on the development of students' creativity was examined by means of a retrospective approach. We investigated whether two influential factors within school education (1) school type (i.e., traditional vs. alternative vs. religious) and (2) perceived teaching style (i.e., independence, judgment, flexibility, integration) associate with students' creativity at university entrance level. The difference was examined at the primary and secondary school level, respectively. Study 1a found that students who attended alternative schools at the secondary school level performed better on divergent thinking tasks as compared to students who attended traditional or religious schools. Relationship between students' creative performance and the perceived teaching styles were inconclusive. Finally, teaching styles in alternative schools during secondary education were perceived as high in independence and flexibility. Study 1b replicated the finding that university students who attended alternative schools during secondary education have an advantage in divergent thinking. Taken together, our results highlight the positive influence of alternative school education on students' creative performance at the university entrance level.